eConsultation in Plastic and Reconstructive Surgery - Trovato, M. J. (Open Science Company, LLC, 2011)
Objective: Early studies of plastic surgery patient triage using telemedicine are descriptive and deal with feasibility rather than accuracy. The inpatient study arm compares on-site wound-evaluation accuracy with remotely viewed digital images. The outpatient arm prospectively compares on-site and remote diagnosis, management, and outcomes in a busy, urban, reconstructive-surgery clinic. The concurrent 6 patient case studies illustrate significant systems improvement by using remote consultation. Methods: A total of 43 inpatients and 100 consecutive outpatients were evaluated by on-site and remote surgeons as performed in previous arms with digital-camera and store and forward technology. Consent was obtained from all patients participating. Agreements regarding diagnosis (skin lesion, hand injury, wound type, and scar character) and management (healing problem, emergent evaluation, antibiotics, and hospitalization) were calculated. Results: In the first study arm, on-site and remote agreement (46%-86% for wound description and 65%-81% for management) generally matched agreement among on-site surgeons (68%-100% and 84%-89%). Moreover, when on-site agreement was low (68% for edema), agreement between on-site and remote surgeons was also low (57%). Remote evaluation was least sensitive detecting wound drainage (46%). On-site surgeons opted for more treatment, often prescribing antibiotics and admitting the patient. The second teleconsult arm provides further evidence of accuracy, overall agreement of 32%, sensitivity 48.55%, specificity 96.92%, positive predictive value 49.26%, negative predictive value 96.83%, and P < .001 regarding diagnosis (skin lesion, hand injury, wound type, wound problem, and scar character). Patient transfer, postoperative monitoring, and outcomes via electronic image transfer, as well as cost-benefit analysis of this clinic-based study, are presented. Conclusions: eConsultation renders similar outcomes to standard, on-site examination in a selected group of plastic surgery patients. Remote evaluation may assist triage decisions, thereby decreasing emergency room throughput time and office-visit frequency, supplementing satellite facility consultation by plastic surgeons, and providing real-time postoperative assessments, thereby improving quality and reducing costs.